Earnings Quality: Before And After Ifrs Adoption - Devianti Yunita, Rusydina Nur Fajrina, Evita Puspitasari, Handiani Suciati, Cahya Irawadi, (Opción, 2019)
This research aims to evaluate whether there is any increasing in financial reporting quality after the IFRS adoption. The population in this research are the companies becoming a member of LQ 45 for the period 2009-2014. In the end, this researh is using 58 sample companies.This reseach is using paired sample test to analyze the data.The result showed that the financial reporting quality after the IFRS adoption was higher than the financial reporting quality before the IFRS adoption. As a conclusion, the financial reporting quality of the Indonesian companies was increasing after the adoption of the IFRS.